Conventional versus ultrasound and microwave assisted synthesis: Some new environmentally friendly functionalized picolinium-based ionic liquids with potential antibacterial activity - Messali Mouslim (Acta Pharmaceutica)
A green chemistry approach has been adopted for the synthesis of thirty-four new picolinium-based ionic liquids using microwave (MW) and ultrasound (US) irradiation as well as conventional thermal heating. Their structures were confirmed by FT-IR, 1H NMR, 13C NMR, 11B NMR, 19F NMR, 31P NMR, mass spectra and elemental analyses. The antimicrobial profile of the novel ionic liquids was evaluated and the minimum inhibitory concentration (MIC) showed their moderate to low antimicrobial activity against eight types of human pathogens.